2022
DOI: 10.1021/acs.iecr.2c00892
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoluminescence and Aggregation-Induced Emission in Bipolar Phenanthroimidazoles: Role of Positional Isomerization-Induced Switching Effect

Abstract: The newborn materials integrated with aggregation-induced emission (AIE) fluorophores, namely PyNPPI-CCz, PyCNPPI-CCz, PyNPPI-NCz, and PyCNPPI-NCz, show intense fluorescence in solution and films. They have good thermal stability (T g /T d , °C: 143/463-PyNPPI-CCz, 156/489-PyCNPPI-CCz, 199/498-PyNPPI-NCz, and 201/501-PyCNPPI-NCz) and exhibit reversible mechanochromism. In the aggregated phase, the restricted intramolecular rotation of phenyl rings reduced the nonradiative relaxation (k nr ) which enhanced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…As same as most reports, powder X-ray diffraction (PXRD) revealed that the MCL (Δ λ max = 64 nm) could be attributed to the morphological transformation of these compounds from crystalline to amorphous states. 42 Subsequently, this group replaced the carbazole unit with TPEs, and the new compounds showed variable emission colors by varying water fractions which can be ascribed to the size effect of different aggregates. 43 Moreover, the position effect represented a great influence on the molecular conformation and stacking fashion in different solid states.…”
Section: Discussionmentioning
confidence: 99%
“…As same as most reports, powder X-ray diffraction (PXRD) revealed that the MCL (Δ λ max = 64 nm) could be attributed to the morphological transformation of these compounds from crystalline to amorphous states. 42 Subsequently, this group replaced the carbazole unit with TPEs, and the new compounds showed variable emission colors by varying water fractions which can be ascribed to the size effect of different aggregates. 43 Moreover, the position effect represented a great influence on the molecular conformation and stacking fashion in different solid states.…”
Section: Discussionmentioning
confidence: 99%